Character Education for Elementary School Students: A Process of Internalizing Religious Values through Nadoman in Sumedang Regency - Supriyadi, Tedi; Hakam, Kama Abdul; Nurdin, Encep Syarief; Kosasih, Aceng; Rukmana, Anin; Saptani, Entan (Mimbar Sekolah Dasar, 2023)
This study delves into the nadoman tradition prevalent among the Sundanese people of Sumedang district, focusing on how religiosity is transmitted among elementary school children through nadoman as a medium for character education rooted in local wisdom. Sumedang district was chosen due to its declaration as the center of Sundanese culture under the “Sumedang as the Sundanese Cultural Center” government program. Utilizing an ethnographic design, the study involved 3 teachers and 30 elementary school students in the North Sumedang sub-district, Sumedang Regency-West Java.  The study identified five significant themes: nadoman as an expression of appreciation for government policies, nadoman as an educational tradition for Sundanese Muslim children, nadoman as local wisdom, nadoman as a means for internalizing values, and the embodiment of students’ religious character through the nadoman tradition. Ultimately, the study concludes that the nadoman tradition plays a vital role in fostering and fortifying the religious character of children involved, contributing to the development of a character education program rooted in local wisdom within formal education institutions.